Differential Effects of Simian Immunodeficiency Virus Infection on Immune Inductive and Effector Sites in the Rectal Mucosa of Rhesus Macaques - Vajdy, Michael (American Society for Investigative Pathology, 2000)
The rectal mucosa, a region involved in human immunodeficiency virus/simian immunodeficiency virus (SIV) infection and transmission, contains immune inductive sites, rectal lymphoid nodules (RLN), and effector sites, the lamina propria (LP). This study was designed to evaluate cell populations involved in rectal mucosal immune function in both RLN and LP, by immunocytochemical analysis of rectal mucosa from 11 SIV-infected (2 to 21 months postinfection) and five naive rhesus macaques. In the rectum, as previously observed in other intestinal regions, CD4(+) cells were dramatically reduced in the LP of SIV-infected macaques, but high numbers of CD4(+) cells remained in RLN indicating maintenance of T cell help in inductive sites. Cells expressing the mucosal homing receptor α4β7 were dramatically decreased in the RLN and LP of most SIV-infected macaques. The RLN of both naive and SIV-infected macaques contained high numbers of CD68 + MHC-II+ macrophages and cells expressing the co-stimulatory molecules B7-2 and CD40, as well as IgM + MHCII+ and IgM + CD40+ B cells, indicating maintenance of antigen presentation capacity. The LP of all three macaques SIV-infected for 2 months contained many B7-2+ cells, suggesting increased activation of antigen-presenting cells. LP of SIV-infected rectal mucosa contained increased numbers of IgM+ cells, confirming previous observations in small intestine and colon. The data suggest that antigen-presentation capacity is maintained in inductive sites of SIV-infected rectal mucosa, but immune effector functions may be altered.